Sunshine Heart C-Pulse: device for NYHA Class III and ambulatory Class IV heart failure. (September 2016) - Black, Matthew C; Schumer, Erin M; Rogers, Michael; Trivedi, Jaimin; Slaughter, Mark S
Advanced heart failure (HF) patients not meeting criteria for ventricular assist device or heart transplant with life-limiting symptoms are limited to medical and resynchronization therapy. The Sunshine Heart C-Pulse, based on intra-aortic balloon pump physiology, provides implantable, on-demand, extra-aortic counterpulsation, which reduces afterload and improves cardiac perfusion in New York Heart Association Class III and ambulatory Class IV HF. The C-Pulse reduces New York Heart Association Class, improves 6-min walk distances, inotrope requirements and HF symptom questionnaires. Advantages include shorter operative times without cardiopulmonary bypass, no reported strokes or thrombosis and no need for anticoagulation. Driveline exit site infections, inability to provide full circulatory support and poor function with intractable arrhythmias remain concerns. Current randomized controlled studies will evaluate long-term efficacy and safety compared with medical and resynchronization therapy.